Culex quinquefasciatus (Diptera: Culicidae) From Florida Transmitted Zika Virus - Smartt, Chelsea T.; Shin, Dongyoung; Kang, Seokyoung; Tabachnick, Walter J. (Frontiers in Microbiology, 2018)
We report a laboratory colony of Culex quinquefasciatus mosquitoes were experimentally able to salivate Zika virus (ZIKV, Flaviviridae; Flavivirus) at 16 days post infection (dpi). ZIKV RNA was detected in bodies and in saliva deposited on filter paper cards with subsequent studies demonstrating the presence of live ZIKV in saliva.